Non-standard employment in South Africa: how have we adapted in the past five years post amendments related to non-standard employment? - Mitchell, Alma Martha (Department of Commercial Law, 2021)
Non-Standard employment in South Africa: How have we adapted in the past five years post the amendments related to non-standard employment? Chapter 1 This chapter introduces the research question. Chapter 2 Focus on legislative history pertaining to non-standard employment. Chapter 3 Review four cases prior to the recent amendments with regard to the protection of non-standard employees. 3.1 Assist Bakery 115 CC v Ngwenya N.O. and Others. 3.2 Enforce Security Group v Mwelase and Others. 3.3 Piet Wes Civils CC and Another v Association of Mineworkers and Construction (AMCU) and Others. 3.4 Assign Services (Pty) Limited v National Union of Metalworkers of South Africa and Others. Chapter 4 Conclusion in response to the research question.